PENGEMBANGAN GAME QUIZIZZ SUBTEMA KEBERAGAMAN BUDAYA BANGSAKU PADA SISWA KELAS IV SDN WONOTIRTO 05 KABUPATEN BLITAR: Game Quiziz untuk siswa kelas IV - Novialita Angga Wiratama (Jurnal Tunas Pendidikan, 2022)
Abstract This research is a type of Research and Development (R&D) development. The subjects of this development research were 22 fourth grade students. The procedure of this research using the Four-D model consists of four stages, namely the stage of definition, design, development and implementation. The researcher's data collectors provided validation sheets and response questionnaires to students. The validation sheet comes from 3 validators, namely material, language and media. The results of the validation assessment of media, language and material experts obtained data that the product developed in the form of a quiz game was valid to be used as a medium in learning without revision. After going through the validation stage and being declared eligible for testing, the quizizz game product was tested on 22 fourth grade students at SDN Wonotirto 5. Students were given evaluation questions to determine the effectiveness of the quizizz game media. Student learning outcomes test scores are calculated using classical completeness. Completeness can be achieved if student learning outcomes reach a value of 75 out of a maximum value of 100, while classical completeness can be achieved if 75% of the number of students in the class have reached a value of 75. From the test results, data obtained that 18 students scored above the KKM and there were 4 students who scored below the KKM. After being calculated using the classical completeness formula, the percentage result is 84%, so it can be concluded that the quizizz game used has been effectively used.